The impact of organizational support for human resources in enhancing sustainable competitive advantage - Qais, Zahraa; Abdlhussin, Safaa J.; Hussein, Hafsa Atallah (Edelweiss Applied Science and Technology, 2024)
The current study aims to examine the effects of organizational support for human resources and their ability to enhance sustainable competitive advantage. The study also seeks to reveal the level of organizational support and sustainable competitive advantage for the sample studied in private colleges, the research sample. The importance of the current study is derived from the importance of the subject of the current study with its studied variables, and the reflection of their effects on sustainable competitive advantage. The problem of the study was raised through some questions, the most important of which was (to what extent is organizational support available to human resources and to what extent are they able to achieve sustainable competitive advantage?) The current study adopted the descriptive analytical approach as it is the optimal approach to survey the opinions of the sample. The questionnaire was the main tool for collecting data in addition to personal interviews and field visits. A random sample was selected and (160) questionnaires were distributed. (154) questionnaires were collected, of which (137) were valid. Some main and sub-hypotheses were developed, the most important of which was (there is a statistically significant correlation and influence between organizational support on the other hand and sustainable competitive advantage). The results were extracted By using some statistical techniques including correlation analysis, regression analysis and structural modeling to test hypotheses through the statistical program ((SPSS V. 28 to analyze the answers. The study reached a set of conclusions, the most important of which is that the impact of organizational support on sustainable competitive advantage, and when employees feel that they are supported by their organization, their sense of satisfaction and happiness at work is enhanced. This can lead to an increase in performance and productivity, which enhances the competitive advantage of the organization in a sustainable manner.